BUDAYA LOKAL DALAM LIBERALISASI PENDIDIKAN - Karsidi, Ravik (The Journal of Society and Media, 2017)
Globalization has mastered almost every area of life. Many people agree with the opinion that globalization Hasan impact either positively or negatively. On the other hand, Indonesia is undergoing asocial and cultural change on the anongoing basis, driven by innovation in science and opening of information from various sources. A wave of change is controlled by the level of technology in both soft and hard technology. As results, technology brings socio-cultural consequences of each. Global culture gave birth to the era of globalization and western culture over uphold rationality while the eastern culture tends to hold value sandreligioustraditions.These problems become opportunities and threats. The public mindset about quality educational afilterdeviceto the influence of foreign culture has not formed properly. There is adown ward trend appreciation and practice of local values as a filter system against the effects of liberalization in particular due to the negative impact of foreign culture.This paper seeks to examine the increased role of local culture in the influence of the liberalization of education as seen from the concept of the implementation of education, strengthening the school as a pillar of socio-cultural system, efforts to improve the education based on ICT, strengthening moral education, manners and character, and mentality, and strengthening education the identity and independence of the nation based on local wisdom.